2021
DOI: 10.1093/mnras/stab1116
|View full text |Cite
|
Sign up to set email alerts
|

Dark acoustic oscillations: imprints on the matter power spectrum and the halo mass function

Abstract: Many non-minimal dark matter scenarios lead to oscillatory features in the matter power spectrum induced by interactions either within the dark sector or with particles from the standard model. Observing such dark acoustic oscillations would therefore be a major step towards understanding dark matter. We investigate what happens to oscillatory features during the process of nonlinear structure formation. We show that at the level of the power spectrum, oscillations are smoothed out by nonlinear mode coupling, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…While we might expect that these differences will further diminish at later redshifts, a substantial delay may be sufficient to reduce the constraining power of the CMB. We furthermore find the oscillatory features present in the initial power spectrum are removed by nonlinear evolution, similar to the results found for ETHOS models with DAO at larger wavenumbers [96]. Lastly, we note that we ran a DAO simulation without running and found that the power spectra remains linear and the halofinder does not find any halos at this redshift.…”
Section: A Halos At Z ∼ 300supporting
confidence: 85%
See 1 more Smart Citation
“…While we might expect that these differences will further diminish at later redshifts, a substantial delay may be sufficient to reduce the constraining power of the CMB. We furthermore find the oscillatory features present in the initial power spectrum are removed by nonlinear evolution, similar to the results found for ETHOS models with DAO at larger wavenumbers [96]. Lastly, we note that we ran a DAO simulation without running and found that the power spectra remains linear and the halofinder does not find any halos at this redshift.…”
Section: A Halos At Z ∼ 300supporting
confidence: 85%
“…7 shows the ratio of the DPS and DAO mass functions to the CDM one (note that this is done with the same mass bins, but plotted at the mean CDM mass per bin). We note that ETHOS models with DAO have oscillations in the halo mass function [96], which could be possible here, FIG. 6.…”
Section: A Halos At Z ∼ 300mentioning
confidence: 64%
“…[90] found that β = 4.8 and c = 3.3 provide a reasonable fit to N -body simulations, while Ref. [91] obtained comparable results (β = 3.0, c = 3.3) in scenarios where dark matter produces acoustic oscillations at small scales. We show our results in Figure 9.…”
Section: Halo Mass Functionmentioning
confidence: 86%
“…axion-like particles, with extremely small masses m ∼ 10 −22 eV [69][70][71][72] (for an early discussion of the cosmological consequences of ultra-light boson particles for dark matter see also [73][74][75][76]) ; or of DM interactions described by e.g. the Lagrangianbased Effective theory of structure formation (ETHOS) [77,78]; or oscillations induced by interactions in the dark sector [72,[79][80][81]. The various beyond-CDM scenarios predict different shapes for the power spectrum suppressions: for example FDM and ETHOS predict oscillations at very small scales (for FDM see for instance [82,83]), contrarily to WDM.…”
Section: Observational Signatures Of Dark Matter Physicsmentioning
confidence: 99%